2009
DOI: 10.1038/eye.2009.177
|View full text |Cite
|
Sign up to set email alerts
|

Central field perimetry of discriminated targets: I. Results for normal individuals using high-contrast targets

Abstract: Purpose A new perimetry method is described to evaluate central vision under multiple hue, illumination, and contrast conditions; results are described for normal individuals using high-contrast targets. Methods For 70 normal eyes of individuals with varying age, the ETDRS chart acuity was determined as well as discriminated target perimetry using high-contrast targets presented for 250 ms at locations up to 101 eccentricity. Retesting was performed to evaluate for learning and repeatability for the thresholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Indeed, it is generally recognized that the ETDRS chart test poorly correlates with activities of daily living [14] (such as driving at night or playing sports outside), since it’s not time-dependent, and as it allows an evaluation of the BCVA only in a pre-determined single high-contrast glare environment. [15] If the widely used ETDRS chart test is poorly reliable in evaluating BCVA in other contrast or luminance conditions for normal eyes, this may be also worse for PLWH. Indeed, these patients have a poor low-contrast visual performance – even without any retinitis [2] – and can also have poor driving performance.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is generally recognized that the ETDRS chart test poorly correlates with activities of daily living [14] (such as driving at night or playing sports outside), since it’s not time-dependent, and as it allows an evaluation of the BCVA only in a pre-determined single high-contrast glare environment. [15] If the widely used ETDRS chart test is poorly reliable in evaluating BCVA in other contrast or luminance conditions for normal eyes, this may be also worse for PLWH. Indeed, these patients have a poor low-contrast visual performance – even without any retinitis [2] – and can also have poor driving performance.…”
Section: Introductionmentioning
confidence: 99%
“…Außerdem wurde die automatisierte Messung der zentralen makulären Netzhautdicke mittels SD-OCT und eine Autofluoreszenz mit anschließender Fluoresceinangiografie durchgeführt. Die Kontrastsehschärfe wurde mittels Central Vision Analyzer (Vimetrics, Media, PA) bestimmt[10]. Es wurden6 Kontraststufen (M1, 2, 3 und G1, 2, 3) bei verschiedenen Lichtstärken untersucht und für jede Kontraststärke ein Dezimalvisus errechnet.…”
unclassified
“…For these reasons, other investigators have suggested that these chart tests are not a useful determination of vision in other contrast or luminance environments, and those measurements are poorly correlated with daily living activities 8,9 that require the patient to assess visual stimuli in multiple lighting, contrast, or glare conditions against a varied background color or luminance. 7 Also, many common daily activities require an individual to react to a visual stimulus with limited time or information. 7,10 Testing of multiple aspects of patients' visual function (such as contrast sensitivity, luminance adaption, color perception, and reading speed) currently must be performed with separate tests and scoring methods.…”
Section: Introductionmentioning
confidence: 99%
“…7 Also, many common daily activities require an individual to react to a visual stimulus with limited time or information. 7,10 Testing of multiple aspects of patients' visual function (such as contrast sensitivity, luminance adaption, color perception, and reading speed) currently must be performed with separate tests and scoring methods. Recently, the Central Vision Analyzer (CVA; Visoptics, LLC, Mechanicsburg, PA, USA) has been introduced and approved by the Food and Drug Administration as a new interactive computer program to perform a comprehensive analysis of the central visual acuity under conditions that simulate environments of real-world activities that are often reported as visually stressful, such as those encountered under mesopic, lighting, or glare photopic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation